STAT signaling in the pathogenesis and treatment of cancer. - Frank, D. A. (The Feinstein Institute for Medical Research, 1999)
Exceptional advances have been made recently in our understanding of the signaling pathways that control cellular growth, differentiation, and survival. These processes are regulated by extracellular stimuli such as cytokines, cell-cell interactions, and cell-matrix interactions, which trigger a series of intracellular events culminating in the modulation of specific genes. STATs are a highly homologous group of transcription factors that are activated by various pathways and regulate many of the genes controlling cellular function. STATs are activated by tyrosine phosphorylation and modulated by serine phosphorylation, placing them at a convergence point for numerous intracellular signaling pathways. Given the importance of STATs in the control of normal physiologic processes, it is not surprising that inappropriate activation of these proteins has been found in human malignancies. A number of distinct mechanisms have been elucidated by which STATs are activated inappropriately, including autocrine or paracrine stimulation of normal receptors and increased activity of tyrosine kinases through enhanced expression, mutations, or the presence of activating proteins. Furthermore, inappropriate STAT serine phosphorylation has been found in several tumors as well. The increased understanding of signaling pathways in tumors can be translated into therapeutic strategies that have the potential to be more selective and less toxic than current anti-cancer treatments. Approaches which may be effective include the development of antagonists of receptors that can trigger STAT activation, inhibitors of the tyrosine and serine kinases that phosphorylate and activate STATs, agents that decrease STAT levels or inhibit their recruitment to kinases, and molecules that can prevent the binding of STATs to target DNA sequences. Thus, elucidation of cellular and biochemical processes in tumors has enhanced our understanding of the pathogenesis of malignancies and may provide the basis for significant advances in therapy.